Extraction of kappa carrageenan from local edible seaweed - Siti Mahira, Ahmad (2014)
Kappa carrageenan is a polysaccharides which can be extracted from red seaweed such as Eucheuma cottoni species. This study report the extraction of kappa carrageenan from local edible seaweed. The effect of various concentrations of extracting solvent (KOH), time and temperatures on kappa carrageenan properties was studied. The KOH solutions ( concentrations 0.03,0.05, 0.1M) were used as extracting solvent. Extraction process was carried out in oil bath with a constant ratio of seaweed weight to solvent volume ( 1:20 g/ml) at temperatures (80, 90, 100 ℃) for 1,2,3, and 4 hours. During extraction process the samples were stirred using magnetic bar and hot plate stirrer for 10 minutes for every half an hour. Then for the isolation process, the potassium chloride (2% w/v) was used to make the kappa carrageenan become precipitated. The precipitated carrageenan were left to dried at room temperature and were kept in desiccators until further analysis. Higher KOH concentration lead lower sulphate content and higher gel strength of extracted carrageenan. In terms of yield the 0.05M KOH, sample C2 (0.05M, 80℃ , 3h) showed the highest yield, while to get highest gel strength the best parameter is L3 ( 0.1M,100℃, 4h)